Routledge Handbook on Gender and Corruption - (:unkn) unknown (My University, 2025)
he Routledge Handbook of Gender and Corruption showcases the most innovative and exciting research being conducted in this area of study, providing a comprehensive go-to reference for all who are interested in the topic. In the last two decades, there has been an increasing awareness of the importance of understanding the nexus between gender and corruption in terms of understanding the way men and women experience corruption and the differential impact of anti-corruption frameworks on men and women, as well as an understanding of how women in different spaces affect the prevalence and kinds of corruption. This Handbook examines these issues as well as the role of social and gender norms in relation to corruption. This understanding is crucial for our ability to design anti-corruption frameworks that are effective and do not create unintended consequences for any group. Despite the importance of this issue, there remains a lack of in-depth, analytical, and geographically diverse investigations into the nexus of gender and corruption. This book addresses this gap by providing a comprehensive, multidisciplinary, geographically balanced treatise on gender and corruption. This book combines sectoral, thematic, and country-specific studies to allow readers to easily compare differing perspectives and approaches on cutting-edge issues and their implications for gender and corruption. Key sectors such as education, politics, public procurement, healthcare, sport, sanitation, and immigration are considered, as well as the role of new technologies, in supporting whistleblowing. This Handbook provides academics, practitioners, and graduate researchers of public policy, public administration, law, and anti-corruption with all of the tools they need to understand the nuances of gender and corruption.
Keywords: Gender; Corruption; Gender Norms; Ethics